Analisis Pengukuran Beban Kerja Fisiologis dan Psikologis Karyawan Produksi Menggunakan Metode CVL dan NASA-TLX Pada Produksi PC-Deck di PT XYZ - Meilani, Dewi; Sofyan, Hady; Kicky Basuki Putri, Pandena (JURMATIS (Jurnal Manajemen Teknologi dan Teknik Industri), 2025)
PT XYZ is one of the precast concrete construction companies located in Purwakarta. On the PC-Deck production line, employees often face complex workloads, both physically and psychologically. This study aims to determine the classification of physiological and psychological workloads of production employees using two methods, namely Cardiovascular Load (CVL) and NASA Task Load Index (NASA-TLX). Physiological workload measurements were conducted by monitoring heart rate during rest and work periods. The results showed that the majority of employees fell into the moderate CVL category (30–60%), indicating that improvements are needed, though not yet urgent. However, one employee had a CVL value of 64%, indicating high physical workload and requiring immediate intervention. On the other hand, NASA-TLX results showed that 6 out of 8 employees had a Weighted Workload (WWL) above 80, indicating extremely high psychological workload. This workload is influenced by a combination of factors, particularly work pressure, workload volume, and long working hours. Proposed improvements include stress and fatigue management training, additional manpower and tools, more structured work planning, and production capacity evaluation.